thinking strategies for activities Sports physical education among players Handball and volleyball players and basketball players (Journal of the College of Basic Education, 2023)
We find many players possess many physical, skillful and tactical capabilities, exceptThey cannot use and employ these abilities when participating in sports competitionsThis is due to their lack of mental skills and abilities and their excitement alongside their other abilities ©While others achieve the best sporting achievements thanks to their use and employmenttheir skills and mental abilities effectively and integratedly during sports competitions.As for the research problem, the researcher found that most of the players cannot use the gameAnd employing their abilities when participating in sports competitions, as a result of their lack ofMental skills and abilities and their stimulation in addition to their other abilities, which causes their inabilityprovide them with the required level.The aim of the research is to identify the relationship between physical and educational sports activitiesThe mental skills of team players.As for the research hypothesis, it is in the following question: What is the relationship of physical sports activitieseducational skills with some mental skills for team players?The researcher used the descriptive survey method. The research was carried out on a sampleThey are chosen according to the intentional method. The researcher explained the methods and tools usedsearch. Scientific tests and measures used in the research are characterized by validity coefficients